Structure, corrosion behavior, and antibacterial properties of nano-silica/graphene oxide coating on biodegradable magnesium alloy for biomedical applications - Bakhsheshi-Rad, H. R. (Elsevier Ltd, 2016)
In the present study, a novel nano-silica (SiO2)/graphene oxide (GO) coating was deposited on Mg alloy via physical vapor deposition (PVD) combined with dip coating. The structural characterization clearly revealed that the nano-SiO2 underlayer had a compact columnar microstructure with a thickness of 1 μm, while the GO overlayer presented a sheet-like morphology with a thickness of around 30 μm. The in-vitro degradation rate revealed that the presence of GO as an overlayer on the nano-SiO2 layer significantly decreased the corrosion rate of the Mg alloy. The antibacterial results demonstrated that the both nano-SiO2/GO and nano-SiO2 coatings exhibited a strong antibacterial activity against the Streptococcus mutans. However, the nano-SiO2/GO coating exhibited better antibacterial activity compared to the nano-SiO2 coated and uncoated samples. These results exhibit that nano-SiO2/GO coating has effective antibacterial activity and high corrosion resistance in vitro, thus, it can be considered as a promising material for implant applications.